Clinical and Morphological Manifestations of Gastritis and Serum Cytokine Levels in Schoolchildren with Familial History of Gastric Cancer - T. V. Polivanova; E. V. Kasparov; V. A. Vshivkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A study of the clinical and morphological traits and cytokine profile of gastritis in schoolchildren with familial history of gastric cancer.Materials and methods. A cross-sectional questionnaire survey was conducted in Siberian regions (Tuva, Even-kiya, Aginskiy Buryat National District, Krasnoyarsk). A total of 3,343 schoolchildren aged 7–17 were surveyed for gastrointestinal complaints and history of gastric cancer in their 1st–2nd degree kindred. Oesophagogastroduo-denoscopy (OGDS) with gastric mucosa biopsy were performed in 463 respondents with complaints. Gastritis was graded in the Sydney classification. Serum cytokine levels (IL-2, IL-4, IL-8, IL-18, IL-1β, IFN-α, TNM-α) were obtained in enzyme immunoassays (ELISA).Results. Schoolchildren with gastritis and familial history of gastric cancer revealed a higher 59.8% rate of dyspeptic complaints vs. 40.8% in negative history (p = 0.001), as well as complaints of weekly heartburn in 14.2 and 8.3% cas-es (p = 0.019), respectively. In positive history and negative H. pylori tests, the cell immune response regulator IL-18 37 was revealed elevated in histology. In histologically verified H. pylori, no cross-cohort differences were observed in serum IL-18 by positive familial history of gastric cancer.Conclusion. Gastritis in schoolchildren with familial predisposition to gastric cancer more often associates with GERD and dyspepsia usually presented in postprandial distress syndrome. The cytokine regulation properties of gastritis in schoolchildren with familial history of gastric cancer have been reported.